The sitch on the parking glitch parking condition in Tacloban City - Abellar, Trixie Nicole; Diaz, Jill Iris; Flores, Regine Mae; Tan,Francis Michael; Yao, Hedy; Exconde, Amy Joan E. (2016)
This research analyzes the state of parking situation in Tacloban City by conducting survey to commuters, PUV drivers, Private-vehicle Owners, and personnel of the Traffic Operations, Management, Enforcement, and Control Office (TOMECO). This research confirms that parking situation in Tacloban City needs to be addressed for it negatively affects the traffic in the city. This study also verifies that the commuters and motorists are not fully aware of the parking ordinances. The lenient implementation of ordinances results to inefficient execution of apprehending violators. Lastly, the unavailability of parking spaces within the city causes traffic congestion. The implementing body and the people should do their respective responsibilities so that efficient parking situation will be achieved.
Undergraduate research (Bachelor of Science in Management) -- University of the Philippines, Tacloban.